EFFECT OF PLANT DENSITIES AND CULTIVARS ON YIELD COMPENENTS OF RAPESEED (Brassica napus L.) UNDER DRY LAND FARMING IN IRAQI NORTHERN - Shaker A.T (Mesopotamia Journal of Agriculture)
The experiment was conducted at the college farm of Agriculture and Forestry – Mosul Univ . for two seasons 2005/2007 , to determine the effect of three plants density (500000 , 333333 and 250000 plants ha-1) with two cultivars (pactol and shiralee) on growth and yield of rapeseed under semi arid condition. The results showed that superiority of no. of seeds/siliqua , seed yield , oil percentage and oil yield with500000 plants ha-1 for both seasons . Pactol cultivar was superior on no. of siliqua/plant , wt. of 500 seeds , seed yield, oil percentage and oil yield for both seasons. The interaction of 500000 plants ha-1 with pactol cultivar gave excellent result on seed and oil yield , which increased up to 4796 and 1759.4kg ha-1 in the first season and up to 3835.3 and 1325.3kg ha-1 in the second season . Correlation between no. of seeds/siliqua and wt. of 500 seeds had positively related to no. of siliqua/plant, while oil yield correlated positively with the seed yield for both seasons .